Od rynku do mallu. Zmiany centrów miast śląskich i ich społeczna percepcja - Nawrocki, Tomasz (Studia Etnologiczne i Antropologiczne, 2010)
The article presents a fragment of the results from the study on the perception of the central space of five Silesian cities: Katowice, Rybnik, Tychy, Bytom and Ruda Śląska, conducted with Krzysztof Bierwiaczonek (PhD, The Institute of Sociology, The University of Silesia). Out of a large research material the author selects a part devoted to the perception of changes in the centres of the cities under examination. The author wondered if, with reference to the places in question, the thesis of the crisis of the city central space is justified, if their traditional centre disappears or is moved to big shopping malls. The studies were qualitative and quantitative in nature. The main research technique was a free interview based on the one conducted by Lynch and Nasar (the studies in Knoxville). The supporting technique constituted a draft of the city central space outlined by the respondents intertwined into the interview. Thanks to it, the mental maps were created, or, to be more specific, cognitive maps of the central space. The results that were discussed concerned the need of the existence of the centre, the replacement of the centre with big shopping malls, the desacralization of the centre and perception of changing ongoing there. The material collected allows to make a statement that despite many symptoms of the transition of the Silesian city centres into the non centres of non cities, the trivialization of their central space has not happened yet. The centres still play an important role in the cities under investigation. The inhabitants appreciate the need of the existence of the centre and perceiving the city a such, refer to the spacious archetype, i.e. the city with the central point the market square constitutes. The studies also showed that malls did not replace the central space. Another conclusion deriving from the research is a progressing desacralization of the central space of the cities in focus.